(untitled) (Revista de Ciências Agroveterinárias, 2018)
Seedling fruit formation is an important stage of fruit production, this also being true for citrus cultivation, especially for producing quality seedlings. The use of alternative sources of mineral nutrients could offer novel fertilizer options for modern agriculture. The objective of this study was to evaluate the growth and development of Rangpur seedlings subjected to water-soluble complex application at different concentrations as an alternative source of mineral nutrients. The experiment was developed from November 2012 to April 2013, and the Rangpur seedlings were stored in plastic tubes during 150 days. The water-soluble complex (WSC) was applied as dressing through monthly irrigation with solutions at concentrations of 0, 1, 2, 4 and 8 g L-1 on seedlings with or without conventional chemistry fertilization. The characteristics evaluated were seedling height, stem base diameter, number of leaves, root length, fresh and dry mass of the aerial part as well as of the root system, total root length, and root volume. The WSC influenced the height and diameter of Rungpur seedlings, whose estimated concentrations between 4 and 8 g L-1 tended to have better results. The dressing with WSC, when compared to conventional chemistry fertilization showed better root formation both in length and volume, except when 8 g L-1 was applied.